LINGUISTIC FOUNDATIONS OF THE PHRASEOLOGY OF THE SPANISH LANGUAGE - Djalilova Sarvaroy Mekhrojovna (Western European Studies, 2024)
The main meaning of the phrase ir a + infinitive as a phraseologized construction, in Presente and Imperfecto de Indicativo, is the expression of the future tense with various shades. Semantic shades of the future tense often depend on the presence of certain circumstances or on the context as a whole. The main meaning of the future tense can be complicated by various modal and aspectual shades. We are talking only about modal or aspectual shades, and not about an independent modal (aspectual) meaning, since the action expressed by the construction is thought of as the future, i.e. the basic meaning of the construction ir a + infinitive is preserved
Keywords: ir a + infinitive; Free phrases; Presente de Indicativo